Periodic Reeb orbits on prequantization bundles - Albers, Peter; Gutt, Jean; Hein, Doris (Journal of modern dynamics, 2018)
In this paper, we prove that every graphical hypersurface in a prequantization bundle over a symplectic manifold M, pinched between two circle bundles whose ratio of radii is less than √2 carries either one short simple periodic orbit or carries at least cuplength (M)+1 simple periodic Reeb orbits.
Gesehen am 25.01.2019